EXTH-82. THERAPEUTIC TARGETING OF EZH2 AND BET BRD4 IN PEDIATRIC RHABDOID TUMORS. (14th November 2022) - Ishi, Yukitomo; Zhang, Yongzhan; Zhang, Ali; Sasaki, Takahiro; Piunti, Andrea; Suri, Amreena; Watanabe, Jun; Abe, Kouki; Natsumeda, Manabu; Zou, Lihua; Shilatifard, Ali; Hashizume, Rintaro
Abstract: BACKGROUND: Aberrant activity of the H3K27 modifiers EZH2 and BRD4 is an important oncogenic driver for atypical teratoid/rhabdoid tumor (AT/RT), and each is potentially a possible therapeutic target for treating AT/RT. Thus, targeting distinct histone modifier activities would be an effective approach for treating AT/RT. METHODS: The effects of EZH2 and BRD4 inhibition on histone modification, cell proliferation, and cell invasion were analyzed by immunoblotting, MTS assay, colony formation assay, and cell invasion assay. RNA- and chromatin immunoprecipitation-sequencing were used to determine transcriptional and epigenetic changes in AT/RT cells treated with EZH2 and BRD4 inhibitors. We treated mice bearing human AT/RT xenografts with EZH2 and BRD4 inhibitors. Intracranial tumor growth was monitored by bioluminescence imaging, and the therapeutic response was evaluated by animal survival. RESULTS: AT/RT cells showed elevated levels of H3K27 trimethylation (H3K27me3) and H3K27 acetylation (H3K27ac), with expression of EZH2 and BRD4, and lack of SMARCB1 proteins. Targeted inhibition of EZH2 and BRD4 activities reduced cell proliferation and invasiveness of AT/RT in association with decreasing H3K27me3 and H3K27ac. Differential genomic occupancy of H3K27me3 and H3K27ac regulated specific gene expression in response to EZH2 and BRD4 inhibitions. Genes associated with DNA-repair pathway was downregulated upon EZH2 and BRD4 inhibition, and the sensitivity to cisplatin was elevated upon combination of EZH2 and BRD4 inhibitors in vitro . A combination of EZH2 and BRD4 inhibition increased the therapeutic benefit in vitro and in vivo, outperforming either monotherapy. CONCLUSION: Histone H3K27me3 and H3K27ac were elevated in AT/RT cells and distributed in distinct chromatin regions to regulate specific gene expression and to promote AT/RT growth. Targeting EZH2 and BRD4 activity is therefore a potential combination therapy for AT/RT.